2003
DOI: 10.1108/02683940310473082
|View full text |Cite
|
Sign up to set email alerts
|

The relationships among individual differences, needs and equity sensitivity

Abstract: The objective of this study is to examine the influence of different facets of needs (i.e. self‐achievement, power, and affiliation needs) on the relationship between individual dispositions (i.e. independence and interdependence of self) and attitudes to equity (i.e. entitled and benevolent). Data were collected from a sample of 243 Japanese university students. Structural equation analysis and simple regression analysis were performed. As a result of structural equation analysis, needs were found to mediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 37 publications
1
40
0
6
Order By: Relevance
“…According to Martin (1984), individuals with a high need for affiliation tend to behave in socially appropriate ways in order to produce favorable evaluations by others and protect their self-concept. In contrast, individuals with a low need for affiliation (independent-oriented individuals) emphasize individual ability and skill above collaborative efforts (Yamaguchi, 2003). These individuals are less likely to conform to others' expectations and tend to perform in ways that promote high internal evaluations of selfworth.…”
Section: Need For Affiliationmentioning
confidence: 80%
See 1 more Smart Citation
“…According to Martin (1984), individuals with a high need for affiliation tend to behave in socially appropriate ways in order to produce favorable evaluations by others and protect their self-concept. In contrast, individuals with a low need for affiliation (independent-oriented individuals) emphasize individual ability and skill above collaborative efforts (Yamaguchi, 2003). These individuals are less likely to conform to others' expectations and tend to perform in ways that promote high internal evaluations of selfworth.…”
Section: Need For Affiliationmentioning
confidence: 80%
“…Further, they receive social gratification through harmonious relationships (Murray, 1983), which explains their need for strong in-group relationships. Sometimes characterized as interdependent orientation (e.g., Wiesenfeld et al, 2001;Yamaguchi, 2003), individuals with a high need for affiliation tend to identify themselves in relation to social networks. According to Martin (1984), individuals with a high need for affiliation tend to behave in socially appropriate ways in order to produce favorable evaluations by others and protect their self-concept.…”
Section: Need For Affiliationmentioning
confidence: 99%
“…James (1993), Yamaguchi (2003), and Allen et al (2005) concluded that cultural difference is a potential factor which impacts opinions, perception and behaviors of employees at workplaces. It should be said that there is no "right" way to deal with cultural difference about perceived organizational justice and equity sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Sauley and Bedeian (2000) have criticized measurement of ES and developed the Equity Preference Questionnaire (EPQ) to address these concerns. Also, Yamaguchi (2003) contended that a forced distribution measurement is not appropriate for measuring psychological states. For this, in future researches, researcher could use Equity Preference Questionnaire (EPQ) in their studies.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation